A 10-kDa class-CI sHsp protects E-coli from oxidative and high-temperature stress - Jofre, A; Molinas, M; Pla, M (PLANTA, 2003)
We report on a new cDNA clone (Qshsp10.4-CI) of a Quercus suber L. class-CI small heat-shock protein (sHsp) obtained from cork (phellem), a highly oxidatively stressed plant tissue. The deduced gene product lacks the C-terminal extension and the consensus I region of the alpha-crystallin domain, being the most C-terminally truncated sHsp reported to date. In an attempt to prove that a protective function is possible for such a truncated sHsp, we overexpressed in Escherichia coli three recombinant sHsp-CIs, one (rQsHsp10.4-CI) showing the same truncation as Qshsp10.4-CI, a second (rN49) lacking the whole alpha-crystallin domain, and a third (rN153) consisting of a full-length sHsp-CI. The overexpression of rN153 and, remarkably, rQsHsp10.4-CI but not rN49 enhanced cell viability under high temperature and, interestingly, under oxidative stress. These results show that the C-terminal extension and the consensus I region of the alpha-crystallin domain are dispensable, but amino acids 1-41 of the alpha-crystallin domain (including the consensus II region) are essential for the protective activity of sHsp-CIs. On the other hand, two-dimensional immunodetection patterns showed accumulation of ca. 10-kDa sHsp-CI immunorelated polypeptides in cork and other oxidatively stressed tissues but not in control and heat-stressed tissues. We discuss the possible role of highly truncated sHsps in relation to oxidative stress.
Keywords: chaperone activity; heat stress; Oxidative stress; Quercus; small heat-shock protein

APLICACION DEL ANALISIS DE IMAGENES AL ESTUDIO DE PARÁMETROS MORFOMETRICOS DEL CORCHO - Campos, M; Molinas, M (Scientia gerundensis, 1999)
In this work we propose a method to study cork quality from little samples throug the analy- sis of images. This method has aplications in all studies that need cork quality determination. The digital analysis of images is an apropiate option due to makes morphometry automati- cally and it allows a quick manipulation of the results. It is a fast and objective method because allows the comparative study between a high number of samples; so it could be pos- sible to compare populations or individual in order to study the influence of some ambiental or getnetic factors and have another aproach to three's selection. Here we describe an digital analysis program based on IMAGE 1.41 VDMi software for Macintosh developed to measu- re severa1 cork morphometric parameters.
Keywords: Cork quality; image analysis; methodology; morphometry; Quercus suber

Efecto de los tratamientos silvopastorales en el crecimiento del alcornoque - Caritat, A; Molinas, M; Vilar, L; Masson, Ph. (Scientia gerundensis, 1999)
Comparative effects of shrub clearing and grazing on the apical and radial growth of the cork oak have been studied in four cork oak wood stations. Shoot growth segments and annual wood rings were measured in 10 selected trees in every plot. Average shoot elongation's oscillate between 2.5 to 4.8 cm; annual wood rings from 0.95 to 2.05 mm and annual radial growth of wood plus cork from 2.3 to 5.7 mm. Significative differences were found between silvo-pastoral treatments in relation to apical elongation. In treated plots, the apical growth of segments that reach the maximum elongation can be a 75% higher than in control plots. This increment on shoot growth can be explained by the decrease in plant competition and by the nutrient contribution of grazing. No significative effects of treatments on radial growth have been found.
Keywords: Alcornoque; crecimiento apical; Crecimiento radial; desbroce; pastoreo (voyant)

Annual cork-ring width variability of Quercus suber L. in relation to temperature and precipitation (Extremadura, southwestern Spain) - Caritat, A; Molinas, M; Gutiérrez, E (Forest Ecology and Management, 1996)
A 14 year sequence of cork-ring width chronology is correlated with rainfall and temperature data. Cork specimens were obtained from three cork peel samplings carried out in 1989, 1991 and 1993 from a cork ‘dehesa’ in Ckeres, Spain. Average width of cork-rings varied between 2.05 and 4.37 mm. The cork-ring width chronologies of the three peel-off samplings show definite agreement patterns. Differences in ring width in years of greater and lesser growth are clearly marked. Correlation between ring width and rainfall indicates that the rain periods with the greatest influence on cork growth are those occurring from November to June, followed by those from November to September. Temperature, on the other hand, shows a negative correlation with cork growth, except during the coldest months and the months of April and September when temperature possibly has a crucial influence on phellogen activation.
Keywords: climatic fluctuations; cork growth; cork-oak; cork-ring chronology; Quercus suber L.

Litterfall and mineral return in two cork-oak forests in northeast spain - Caritat, A; Bertoni, G; Molinas, M; Oliva, M; Domínguez-Planella, A (Ann. For. Sci., 1996)
Seasonal trends in littertall and potential mineral return were studied in two cork-oak forest sites in the northeastern Iberian peninsula. The estimated average litter production was 3.9 Mg.ha-1.year -1 for one site and 4.6 Mg.ha-1.year-1 for the other; these figures are similar to those reported for holm-oak (Quercus ilex) forests in the same area. Seasonal litterfall patterns were typical of Mediterranean forest ecosystems. Leaves accounted for 46 to 78% of the total dry matter. Their annual weighted-average mineral composition was low in macronutrients (N 8-9; K 4-5; Mg 0.8-1.3; Ca 9-10 and P 0.4-1 mg.g-1) and relatively high in micronutrients such as Mn (2-2.2 mg.g-1) or Fe (0.3-0.4 mg.g-1). Minimum N and P concentrations were found during the growth period. Estimates of potential mineral return for an annual cycle were N 38-52, P 2.1-5.2, K 20-28, Ca 44-53 and Mg 5.4-5.0 kg.ha -1, depending on the site biomass and fertility.
Keywords: cork-oak; litterfall; Mediterranean forest ecosystems; nutrient cycling; Quercus suber

Nutrient content and seasonal fluctuations in the leaf component of coark-oak (Quercus suber L.) litterfall - Robert, B; Caritat, A; Bertoni, G; Vilar, L; Molinas, M (Plant Ecology, 1996)
Nutrient content and seasonality of the leaf component in cork-oak litterfal were studied over a two year period in two cork-oak forest sites differing in biomass and edaphic condition in the north-eastern Iberian peninsula. Fallen senescent leaves compared to young leaves showed higher non-mobile nutrient concentrations and lower mobile nutrient concentrations, specially P, N, K, and Mg. At both sites, seasonal fluctuations affected both leaf production and leaf mineral content. The maximum leaf fall period correspond to the start of the vegetative growth and to the lowest N and P concentration in the falling leaves. The opposite was true for the winter, when litterfal was minimal and N and P content in falling leaves was at a maximum. The comparison between falling leaves and canopy leaves suggests that the analysis of fallen leaves can be a useful measure of N and P nutrition in cork-oak. We found site dependent differences in nutrient content and nutrient remobilization. In comparison with Q. ilex, although litter production was in the same range, nutrient retranslocation was greater for Q. suber.
Keywords: litterfall; nutrient return; nutrients in leaves; Quercus Suber L; retranslocation; seasonal trends

APLICACION DEL ANALISIS DIGITAL DE IMAGENES AL ESTUDIO DE LA CALIDAD DEL CORCHO - Molinas, M; Campos, M (Congreso Forestal Español, Lourizán - Pontevedra. 1993, 1993)
Digital Image Processing and Analysis (lA) es a computerized technique that permits to measure defined regions of interest of an image. For Al, digital images of the specimens are examined with appropiate software programs. In the present study an lA program for the quuantitative anatomy of cork has been developed. For this purpose IMAGE 1.41 VDM software for Macinstosh and Statview statistic software have been selected. Specimens from different cork populatins have been compared. The following cork parmeters: thickness, cork-rings and prososity have been measured in transverse and tangential sections. The results are analysed comparatively on each population and between populations.
Keywords: Cork quality; image analysis; morphometry; Quantitative anatomy; Quercus suber L.

Estudio preliminar del crecimiento del alcornoque en la fase juvenil. - Oliva, M; Molinas, A Caritat M; Caritat, A; Molinas, M (SCIENTIA gerundensis, 1989)
Shoot elongation has been measured in two different groups of juvenil cork-oaks (Quercus suber) by means of their budding segments. One group has got 14 seedlings three years old, proceeding from a forest nursery. The other group consistes in 17 sprouts of three and one years old from a bumed cork-oak forest. Buddings segments of the three- years old seedlings show an average elongation of 4,l cm. Sprouts are more vigorous; the three years old ones have an average value of segment elongation of 6,05 cm, and the one year old ones an average value of 15,3 cm. A decrease in elongation appears along the succesive buddings
Keywords: buds; cork-oak; Quercus suber; shoot elongation; sprouts

ORGANIZACION Y VARIACIONES ESTACIONALES DEL ÁPICE VEGETATIVO DEL ALCORNOQUE - Molinas, M; Oliva, P; Vázquez, M Oliva P (Scientia gerundensis, 1989)
This paper is directed to the basic understand of organization and seasonal changes in the vegetative buds of the cork-oak through the study of the phenology and the histology of a branch during to annual cycles. During the period under study, two sprouting seasons succeded each year; one sprouting was allways in the middle of the spring and the other one either in the summer or in the fall. The elongation of the branch segments was characteristic of a cork-oak in juvenil phase. The hight value of the whole growth should be noticed. The cork oak produces both short and long shoots. Long shoots occur at the apex and distal portions of branches. The long and short shoots differ in number of leaves but not in internode elongation. Elongation depend on the shoot vigor and position. There is a good correlation between elongation and number of leaves per segment. Buds show seasonal changes. A rest phase, a bud expansion phase and a new bud formation phase partially omerlaping the bud expansion phase can be distinguished. Cork-oak vegetative buds show a tunica and corpus type of cellular zonation which corresponds to the Type I of the Gifford and Carson (1971) classification. Only lowermost leaves ovenvinter in the bud. This may explain the maked heteroblastia of the leaves in the shoots. The seasonal study shows that maximum cytohistological zonation occurs near the end of rapid shoot elongation.
Keywords: bud morphology; cork-oak; Phenology; Quercus suber; shoot elongation

Crecimiento longitudinal del alcornoque: segmentos y hojas - Caritat, A; Molinas, M; Oliva, M (SCIENTIA gerundensis, 1988)
This paper is directed to the basic understand of longitudinal growth of the cork-tree Quercus suber L. Branch constitution is analized through the relation of segments and leaves. To duly recognize segments in branches, an apropiate nomenclature is used. Segments length changes from 0,2 to 11,6 cm, with an average of 2,3 cm. Two kind of shoots, long and short shoots, can be distinguished. Segment elongation tend to decrease as succesive periods accumulate. No differences in segments can be related to the period of the year in which they were developed. Leaves show heteroblastic distribution. Leave lamina has an average length of 3,3 cm and is 2,O cm wide. Petiol is very constant with an average of 0,6 cm.
Keywords: branch growth; cork-tree; leaves; Quercus-suber; shoots